HUSBAND’S SUPPORT PARTICIPATION FOR PREGNANT WOMEN THROUGH VIDEO IN FE TABLET CONSUMPTION - Utami Dewi; Fidyah Aminin; Nurniati TR; Vina Jayanti (SEAJOM: The Southeast Asia Journal of Midwifery, 2020)
The Indonesian government has initiated the provision of iron tablet supplementations to pregnant women. However, the lack of support from the family, especially husbands, in controlling the consumption of these tablets has resulted in the government program not being able to achieve the target set. This quasi experimental study used a pre-posttest model with a control group design. In this study, there were two groups, namely the treatment group and the control group who were given a questionnaire before and after the intervention. The treatment group was given intervention in the form of a husband's mentoring video, while the control group received services in the form of health education with sample size for each group at 47 persons. The results of the analysis showed there were more respondents who experienced the increased knowledge, i.e., 30 persons when compared to those in the control group by only 16 persons. It was then concluded that the use of video to increase the participation of husbands as a companion to remind the wife to consume iron supplementation was significant.